Knowledge on the structure of the solar system in teacher education students: the role of national context and gender - Melis, Claudia; Falcicchio, Gabriella; Wold, Per-Arvid; Billing, Anna Maria (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2024)
For many centuries, humanity believed the Earth to be the center of the Universe with the Sun and the planets orbiting around it (geocentric model). The Copernican revolution proved all planets in the solar system are instead orbiting around the Sun (heliocentric model). Since Copernicus time, our knowledge has improved exponentially, also thanks to the possibility to observe the solar system from space. The solar system is an essential topic in science literacy, necessary to understand how we measure time and what makes the Earth suitable for life. However, we did not know whether our students retained a basic astronomical knowledge from previous education. Before teaching had started, we asked students in Early Childhood Education Norway (n = 102) and Educational Science in Italy (n = 104) to draw the solar system and classified each student’s drawing according to a 10 points scale. According to the drawing-writing method of assessing students, we assumed that the drawings would reflect their level of knowledge. Based on this classification, we could assign to each student a score ranging from zero to nine. We then fitted a generalized linear model to the model explaining score variation with nationality and gender. The best model explaining knowledge included as explanatory variables nationality, gender, and their interaction. Being male and Norwegian was associated with higher knowledge score. The gender effect was significant only for the Italian students. These results might be consequence of both differences in gender equality and teaching programs between the two countries.